Survival Rate Silver Pompano (Trachinotus blochii) with Consentration Sargassum sp. flour that different on feed (Jurnal Intek Akuakultur, 2019)
The study was used repelleting artificial feed with different consentrationSargassum sp. flour. The purpose of this research were to known the effect ofSargassum sp. On different consentration to the Survival rate of silver pompano.This research were held on June-July 2018 for 30 days at the Batam MarineAquaculture Center, Setokok Island , Batam City, Riau Islands. The method wasused experimental with a manual analysis were showed that Sargassum sp. Notgiven effect to the Survival rate of silver pompano. The result were showed that Ctreatment (40 g/kg) have the best on research parameters like absolute weight, andsurvival rate. They were 8,75Â±2,61 g, 93,33Â±0,00 % respectively.